2017
DOI: 10.1016/j.molmet.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A high-content small molecule screen identifies novel inducers of definitive endoderm

Abstract: ObjectivesHuman embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) can generate any given cell type in the human body. One challenge for cell-replacement therapy is the efficient differentiation and expansion of large quantities of progenitor cells from pluripotent stem cells produced under good manufacturing practice (GMP). FOXA2 and SOX17 double positive definitive endoderm (DE) progenitor cells can give rise to all endoderm-derived cell types in the thymus, thyroid, lung, pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…The results confirmed the presence of T+/SOX9+ NLC up to day 7 when NOTO was transfected (7.6%, Figure 5C,D and Figure S1). In the course of hiPSCs differentiation, FOXA2+ is also indicative of the presence of nascent definitive endoderm cells, which co-express SOX17 at early stages [51,52]. Consistent with our RT-qPCR results, FOXA2-transfected cells had a propensity to differentiate into definitive endoderm cells as compared to those transfected with NOTO (45.6% and 26.2% of FOXA2+/SOX17+ cells at day 7 respectively; Figure 5C,D and Figure S1).…”
Section: Noto Transcription Factor Triggers Mepc Commitment Toward Nosupporting
confidence: 85%
“…The results confirmed the presence of T+/SOX9+ NLC up to day 7 when NOTO was transfected (7.6%, Figure 5C,D and Figure S1). In the course of hiPSCs differentiation, FOXA2+ is also indicative of the presence of nascent definitive endoderm cells, which co-express SOX17 at early stages [51,52]. Consistent with our RT-qPCR results, FOXA2-transfected cells had a propensity to differentiate into definitive endoderm cells as compared to those transfected with NOTO (45.6% and 26.2% of FOXA2+/SOX17+ cells at day 7 respectively; Figure 5C,D and Figure S1).…”
Section: Noto Transcription Factor Triggers Mepc Commitment Toward Nosupporting
confidence: 85%
“…Limiting cell movement, by inhibition of Rho-associated protein kinase (ROCK), an important controller of actin microfilaments, did not affect the differentiation to Sox17+ cells nor their proliferation, regardless of the timing of inhibition. It was previously shown that ROCK inhibition and cytoskeletal reorganization can mediate activation of Wnt signaling and the induction of EMT, and can affect cell differentiation in vitro [33][34][35]. While ROCK inhibition early in differentiation may induce EMT and mesendoderm differentiation and by that enhance Sox17 expression later on, the emergence of a similar fraction of Sox17+ cells when ROCKi is added later in differentiation indicates that Sox17 expression does not require cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…They can efficiently promote cell differentiation and govern other cellular activities like common promoters and growth factors which are expensive, and can be harmful. Small molecules are cell permeable chemical compounds which are generally safer, inexpensive, pure, amenable to scaling up, and are devoid of animal derived products which makes them more suitable candidates to be used in in vitro practices [29][30][31][32]. The main motivation behind using small molecules is that they can be synthesized in large amounts with higher purity and stored in a way that ensures their reproducible activity [30].…”
Section: Small Moleculesmentioning
confidence: 99%
“…Small molecules are cell permeable chemical compounds which are generally safer, inexpensive, pure, amenable to scaling up, and are devoid of animal derived products which makes them more suitable candidates to be used in in vitro practices [29][30][31][32]. The main motivation behind using small molecules is that they can be synthesized in large amounts with higher purity and stored in a way that ensures their reproducible activity [30]. Small molecules have been efficiently used in differentiation processes, as they regulate cellular processes by inflecting signal transduction pathways, metabolism, or gene expression.…”
Section: Small Moleculesmentioning
confidence: 99%
See 1 more Smart Citation